Adiposity, dyslipidemia, and insulin resistance in mice with targeted deletion of phospholipid scramblase 3 (PLSCR3) - Wiedmer, Therese (National Academy of Sciences, 2004)
The phospholipid scramblases (PLSCR1 to PLSCR4) are a structurally and functionally unique class of proteins, which are products of a tetrad of genes conserved from Caenorhabditis elegans to humans. The best characterized member of this family, PLSCR1, is implicated in the remodeling of the transbilayer distribution of plasma membrane phospholipids but is also required for normal signaling through select growth factor receptors. Mice with targeted deletion of PLSCR1 display perinatal granulocytopenia due to defective response of hematopoietic precursors to granulocyte colony-stimulating factor and stem cell factor. To gain insight into the biologic function of another member of the PLSCR family, we investigated mice with targeted deletion of PLSCR3, a protein that like PLSCR1 is expressed in many blood cells but which, by contrast to PLSCR1, is also highly expressed in fat and muscle. PLSCR3(-/-) mice at 2 months of age displayed aberrant accumulation of abdominal fat when maintained on standard rodent chow, which was accompanied by insulin resistance, glucose intolerance, and dyslipidemia. Primary adipocytes and cultured bone-marrow-derived macrophages from PLSCR3(-/-) mice were engorged with neutral lipid, and adipocytes displayed defective responses to exogenous insulin. Plasma of PLSCR3(-/-) mice was elevated in non-high-density lipoproteins, cholesterol, triglycerides, nonesterified fatty acids, and leptin, whereas adiponectin was low. These data suggest that the expression of PLSCR3 may be required for normal adipocyte and/or macrophage maturation or function and raise the possibility that deletions or mutations affecting the PLSCR3(-/-) gene locus may contribute to the risk for lipid-related disorders in humans.